ESTIMATING AND ANALYZING THE IMPACT OF SOME MONETARY POLICY VARIABLES ON THE TRADE BALANCE IN IRAQ FOR THE PERIOD 2005-2021 - Ramadan Ali Hussein Al-Jubouri; Hamid Hassan Khalaf (Scholar Express Journals, 2023)
The research aims to show the extent of the impact of some monetary policy tools on the balance of payments in the Iraqi economy during the period (2005-2021) in order to identify the defects and negative points that hinder the achievement of a high growth rate. . There is a positive and significant relationship between some monetary policy tools as independent variables and the balance of payments as a dependent variable in the Iraqi economy during the study period. By pursuing an integrated economic policy through which it works to stimulate private investment of all kinds, whether local or foreign, by providing the requirements of an appropriate investment environment, which in turn works to raise the efficiency of the private sector and increase its contribution to The formation of the gross domestic product, especially in the productive sector of the Iraqi economy and thus the balance of payments
Keywords: monetary policy; balance of payments; economic growth